PENGARUH SELF-COMPASSION DAN EMOTION REGULATION TERHADAP QUARTER LIFE CRISIS PADA MAHASISWA TINGKAT AKHIR - Ifa Ditta Arimindani; Muslikah (IKIP Siliwangi, 2026)
This study aims to examine the influence of self-compassion and emotion regulation on quarter-life crisis among final-year university students. A quantitative correlational design was employed, involving a population of 1,347 students from the Faculty of Education and Psychology, Universitas Negeri Semarang, with a sample of 308 students selected through random sampling. The research instruments included the Self-Compassion Scale (Neff, 2003) consisting of 26 items, the Emotion Regulation Questionnaire (Gross & John, 2003) with 10 items, and the Quarter-Life Crisis Scale (Robbins & Wilner, 2001) with 26 items. Validity testing indicated that all items met the validity criteria, with item-total correlations ranging from 0.21 to 0.59 for the Self-Compassion Scale, all items on the Emotion Regulation Questionnaire confirmed as valid through confirmatory factor analysis, and correlations ranging from 0.264 to 0.682 for the Quarter-Life Crisis Scale (p < 0.05). Reliability testing showed Cronbach’s alpha coefficients of 0.872, 0.790, and 0.854, respectively. Multiple linear regression analysis revealed that self-compassion and emotion regulation had a significant effect on quarter-life crisis, accounting for 83.5% of the variance. Partially, self-compassion had a significant negative effect, expressive suppression had a significant positive effect, while cognitive reappraisal was not significant. These findings suggest that self-compassion serves as a protective factor, whereas less adaptive emotion regulation strategies increase the risk of quarter-life crisis. This study provides a basis for university counselors to develop interventions focusing on enhancing self-compassion and emotion regulation. Future research is recommended to examine additional factors beyond the variables investigated in this study.